Traffic Information Collection Using Wireless Sensor Network Positioning Technology. (6th September 2021) - Zhang, Jinxi; Zhu, Wenying; Wu, Xueying; Ma, Tianshan
Abstract : The wireless sensor network integrates sensor technology, microelectromechanical technology, distributed information processing technology, and wireless communication technology. In order to solve this problem, this paper designs and proposes an anchor node self-location algorithm. Aiming at the positioning accuracy of wireless sensor network nodes, this paper proposes an improved algorithm for sensor network node positioning that uses error correction methods to reduce accumulated distance errors and positioning errors. In this paper, the designed routing algorithm is simulated and implemented, and the performance of the routing algorithm is evaluated based on different network topologies. From the analysis results, compared with the existing typical routing algorithms, the routing algorithms designed in this paper can effectively reduce the energy consumption of the network and prolong the lifetime of the network. The core of the algorithm is to integrate the known and available information of the system to locate unknown anchor nodes. This greatly reduces the number of anchor nodes whose initial position information is required by the system, and under the condition of less impact on the positioning accuracy of the system, the cost of the system is reduced and the scope of application of the system is improved. This paper has deeply studied the positioning and tracking problems in wireless sensor networks, including node positioning, biochemical gas source positioning, and target tracking, and designed and developed a platform for positioning and tracking application research to lay the foundation for further application research. In the study of the above problems, new methods of positioning and tracking with theoretical and practical value are proposed for different practical application scenarios, and the performance is verified and evaluated through computer simulation.